The effect of a pressure ventilatory support on quadriceps endurance is maintained after exercise training in severe COPD patients. A longitudinal randomized, cross over study - Labeix, Pierre; Court Fortune, Isabelle; Muti, Daniela; Berger, Mathieu; Chomette-Ballereau, Stéphanie; Barthelemy, Jean Claude; Féasson, Léonard; Costes, Frédéric (Frontiers in Physiology, 2022)
Purpose: In severe chronic obstructive pulmonary disease (COPD) patients, the application of an inspiratory pressure support (IPS) during exercise increases exercise tolerance and the benefit of exercise training during pulmonary rehabilitation (PR). Moreover, it improves quadriceps endurance after a session of cycling exercise suggesting a reduced muscle fatigue. We looked for the persistence of this effect after PR and sought an association between the improved quadriceps endurance with IPS and the training load during PR. Patients and methods: We studied 20 patients with severe COPD (6 in stage 3 and 14 in stage 4 of GOLD) before and after PR. As part of a PR program, patients completed 16 cycling sessions over 6 weeks with the addition of IPS during exercise. As a surrogate of muscular fatigue, quadriceps endurance was measured at 70% of maximal strength in a control condition, after a constant work rate exercise test (CWR) with IPS (TlimQ IPS) or with a sham ventilation (TlimQsham), in a random order. These tests were repeated similarly at the end of PR. Results: PR was associated with a significant increase in maximal power output, cycling endurance, quadriceps strength and endurance. Session training load (power output x duration of the session) increased by 142% during the course of the program. Before PR, CWR duration increases with IPS compared to sham ventilation (time=+244s, p=0.001). Compared to control condition, post-exercise TlimQ reduction was lower with IPS at isotime than at the end of CWR or than with sham ventilation (-9±21%, -18±16% and -23±18%, respectively, p = 0.09, p<0.0001 and p<0.0001). After PR, the post-exercise decrease of TlimQ was reduced after IPS compared to sham (-9±18% vs -21±17 %, respectively, p=0.004). No relationship was found between the prevention of quadriceps fatigue and the training load. Conclusion: In severe COPD patients, the beneficial effect of a ventilator support on quadriceps endurance persisted after PR with IPS. However, it was not related to the increase in training load, and could not predict the training response to non-invasive ventilation during exercise.